Arsenic in Latin America: New findings on source, mobilization and mobility in human environments in 20 countries based on decadal research 2010-2020 - Bundschuh, Jochen; Armienta, Maria Aurora; Morales-Simfors, Nury; Alam, Mohammad Ayaz; López, Dina L.; Delgado Quezada, Valeria; Dietrich, Sebastian; Schneider, Jerusa; Tapia, Joseline; Sracek, Ondra; Castillo, Elianna; Marco Parra, Lue-Meru; et al. (Critical reviews in environmental science and technology, 2021)
Today (year 2020), the globally recognized problem of arsenic (As) contamination of water resources and other environments at toxic levels has been reported in all of the 20 Latin American countries. The present review indicates that As is prevalent in 200 areas across these countries. Arsenic is naturally released into the environment and mobilized from geogenic sources comprising: (i) volcanic rocks and emissions, the latter being transported over thousands of kilometers from the source, (ii) metallic mineral deposits, which get exposed to human beings and livestock through drinking water or food chain, and (iii) As-rich geothermal fluids ascending from deep geothermal reservoirs contaminate freshwater sources. The challenge for mitigation is increased manifold by mining and related activities, as As from mining sites is transported by rivers over long distances and even reaches and contaminates coastal environments. The recognition of the As problem by the authorities in several countries has led to various actions for remediation, but there is a lack of long-term strategies for such interventions. Often only total As concentration is reported, while data on As sources, mobilization, speciation, mobility and pathways are lacking which is imperative for assessing quality of any water source, i.e. public and private.